Auskultasi Jarak Jauh untuk Pengukuran dan Perekaman Sinyal Suara Jantung - Eka Sari Oktarina; Ira Puspasari; Jusak Jusak (Jurnal Rekayasa Elektrika, 2018)
In 2014, the Sample Registration System (SRS) released a survey showing that heart diseases can be categorized as the second highest non-communicable disease in Indonesia. The percentage is 12.9%. In this work, a tele-auscultation system for heart sound signals was built to transmit the signal over the global Internet networks and store them in a Cloud storage. Thus, the system allows measurement of heart sound signal for the rural area where the presence of expert is very scarce and helps the expert doctors to perform clinical analysis anywhere. Our examination showed that the system exhibited the average transmission delay of 5.68 second and data lost of only less than 1% for transmission of 1 heart sound signal. On the other hand, examination using two heart sound signals transmitted simultaneously showed that it displayed a smaller average of transmission delay. It may be caused by the measurement of the transmission delay as well as data lost that is depended on the traffic in the internet networks. Moreover, correlation of the heart sound signals before and after transmission showed a strong correlation where the correlation value is very close to 1 at, indicating that there is a strong similarity between the two signals.